Legal issues in sharī‘ah-compliant home financing in Malaysia: a case study of a Bai Bithaman Ājil contract - Oseni, Umar Aimhanosi; Ayob, Mohd Fairullazi; Abdul Rashid, Khairuddin (Emerald Publishing Limited, 2019)
This chapter provides a case study on a Sharī‘ah-compliant house facility contract based on the Bai Bithaman Ājil (BBA) contract, generally used by Islamic banks in Malaysia. The study emphasises on the need to comply with the existing legal framework and execute relevant contracts in line with the Sharī‘ah resolutions of the Sharī‘ah Advisory Council of Bank Negara Malaysia without causing harm (ḍarar) to the customers or introducing uncertain elements or procedures (gharar) in the execution of the agreements. This chapter is based on doctrinal analysis of the relevant issues as well as a qualitative legal research through content analysis of relevant BBA agreements, case law as well as statutory provisions. The case study used in this chapter is completely anonymised. The study finds that the execution of BBA agreements in Malaysia leaves much to be desired. Even though the regulatory framework for Sharī‘ahcompliant home financing in Malaysia is robust, there are some legal and Sharī‘ah considerations which the stakeholders need to look into in order to project Malaysia as the main global hub of Islamic finance. This study demonstrates the need for proper Sharī‘ah auditing of the practical execution of BBA agreements to avoid an incorporated element of gharar at the time of execution of the agreements, which might ultimately lead to unforeseen reputation risks for the bank. Though there are several studies on the Sharī‘ah, financing and accounting aspects of the BBA housing facility agreement, this study focusses on both Sharī‘ah and legal issues, using the case study approach. The recommendations are expected to provide a good policy framework for the stakeholders in the Islamic financial services industry in Malaysia.